Scientific Opinion on the update of the list of QPS‐recommended biological agents intentionally added to food or feed as notified to EFSA1. (14th March 2017) - ,; Ricci, Antonia; Allende, Ana; Bolton, Declan; Chemaly, Marianne; Davies, Robert; Girones, Rosina; Herman, Lieve; Koutsoumanis, Konstantinos; Lindqvist, Roland; Nørrung, Birgit; Robertson, Lucy; et al.
Abstract: EFSA is requested to assess the safety of a broad range of biological agents in the context of notification for market authorisation as sources of food and feed additives, food enzymes and plant protection products. The qualified presumption of safety (QPS) assessment was developed to provide a harmonised generic pre‐assessment to support safety risk assessments performed by EFSA's scientific Panels. The safety of unambiguously defined biological agents (at the highest taxonomic unit appropriate for the purpose for which an application is intended), and the completeness of the body of knowledge are assessed. Identified safety concerns for a taxonomic unit are, where possible and reasonable in number, reflected as 'qualifications' in connection with a recommendation for a QPS status. The list of QPS recommended biological agents was reviewed and updated in the current opinion and therefore becomes the valid list. The 2016 update reviews previously assessed microorganisms including bacteria, yeasts and viruses used for plant protection purposes following an Extensive Literature Search strategy. The taxonomic units related to the new notifications received since the 2013 QPS opinion, were periodically evaluated for a QPS status and the results published as Statements of the BIOHAZ Panel. Carnobacterium divergens, Lactobacillus diolivorans, Microbacterium imperiale, Pasteuria nishizawae, Pediococcus parvulus, Bacillus flexus, Bacillus smithii, Xanthomonas campestris and Candida cylindracea were recommended for the QPS list. All taxonomic units previously recommended for the 2013 QPS list had their status reconfirmed as well their qualifications with the exception of Pasteuria nishizawae for which the qualification was removed. The exclusion of filamentous fungi and enterococci from the QPS evaluations was reconsidered but monitoring will be maintained and the status will be re‐evaluated in the next QPS Opinion update. Evaluation of bacteriophages should remain as a case‐by‐case procedure and should not be considered for QPS status. Abstract : This publication is linked to the following EFSA Journal article:http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2017.4663/full, http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2017.e15031/full